Perbandingan Tingkat Kebugaran Lansia Di Panti Wredha Pacitan Dan Di Masyarakat Desa Mbalong Sidoharjo - Dinar Prastica, Yurike; , Yulisna Mutia Sari SSt. FT, M.Sc; , Maskun Pudjianto, SMPh, SPd, M.Kes (2016)
Background: Fitness condition in the elderly is one of the indicators that can be used to determine the level of health in the elderly. By doing programs or activities like sports, it can aim to maintain or improve physical fitness, such as flexibility, strength, endurance, range of motion, balance and muscle coordination are better. Basically the fitness level of wredha elderly homes will be different fitness levels elderly residing in the community. The Objective of Research: To compare the level of fitness of the wredha elderly homes and in the community. The Benefit of Research: Increase knowledge about how comparative level of fitness of the wredha elderly homes and in the community. The Method of Resear in the Cross Sectional research plan. Technically the taking of the sample in a manner Simple Random Sampling with criterian insklusion and eksklusion. The number sample of 30 respondents. Measuring the level of fitness of elderly is to use the six-minute walk. Analysis of the data in this study using a test that is test data normality Shapiro Wilk test. Result of the Research: Based on the analysis of comparative test with Mann Whitney test obtained value of p = 0,028. A p value< 0.05 then the decision is Ha rejected, which means there is have comparison fitness levels in the wredha elderly homes Pacitan and in Mbalong Village Community Sidoharjo. Conclusion: There is a comparison of the level of fitness in the wredha elderly homes Pacitan and Mbalong Village Community Sidoharjo.